The Influence of Spiritual Intelligence and Emotional Intelligence on Job Satisfaction and Nursing Performance - Komang Trisna Sari Dewi (International Journal of Social Science and Business, 2020)
Hospital is one of the public service places engaged in the field of health services where there is a lot of interaction between nurses and patients. Nurses are required to have the ability to manage emotional intelligence and spiritual intelligence possessed. The purpose of this study was to determine the influence of emotional intelligence and spiritual intelligence on job satisfaction and nurse performance at Buleleng General Hospital. The samples of this study were 76 respondents selected by using probability sampling techniques. The data analysis technique used in this study was a structural equation model based on variance and component based SEM with smartPLS 3.0 analysis tools. Based on the result of hypothesis testing shows that emotional intelligence has a significant positive effect on job satisfaction. Second, emotional intelligence has a significant positive effect on nurse performance. Third, spiritual intelligence has a significant positive effect on job satisfaction. Fourth, spiritual intelligence has a significant positive effect on nurse performance.